(3cJGH aj GdWHs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s ((3Hgef Hf Ydj GdcGRQhfj s)
(3ChdgG (B:s
(3UaI bQU GdWHGTjQ GdfGaY ef GdMei hGdYWT hGdGYJOGd jDNP WHGTjQ CQHYI OQGge dH HRQ GdbKGA hGdNjGQ hGdbdY, ef cd hGMO KdGKI OQGge s
(3BNQgG (B:s
(3aEf ef cd hGMO KdGKI OQGge KeGfjI OQGge HRQ MeGV hfbU fGaY dPjP s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B31s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B198 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs